Affective Evaluation of One's Own and Others' Body Odor: The Role of Disgust Proneness. (December 2017) - Übel, Sonja; Wabnegger, Albert; Arendasy, Martin; Zorjan, Sasa; Schienle, Anne
Disgust is part of a behavioral immune system that helps to detect pathogens. One important input to this system is the sense of smell. We conducted an experiment on body odor perception with 72 participants (35 men, 37 women; mean age = 24 years), who had been divided according to high versus low disgust proneness. All participants were exposed to six samples of axillary sweat from other individuals and to their own sweat. They were asked to identify their own body odor and to rate their affective experience. The participants were not able to identify their own sweat; however, differentiation of self versus others was based on experienced disgust; the sweat of others was perceived as more disgusting. Moreover, disgust-prone participants showed differential affective responses to the two sweat sources and evaluated others' sweat as more negative and arousing. The current study points to the important role of state/trait disgust in the implicit processing of body odor.